Analisis Permasalahan Transportasi Perkotaan: Studi Kasus: Jalan Basuki Rachmat pada Area U-Turn Rumah Makan Pagi Sore Palembang - A.Bayu Adi Pratama B.; Prisca Yeniyati; Yohanes Johen; Dustin Nicholas Putra (Universitas Muhammadiyah Palembang, 2025)
Congestion is one of the city's problems that really disrupts travel activities. One of the worst traffic jams in Palembang City occurs in the u-turn area in front of the Morning and Sore Restaurant, Jalan Jenderal Basuki Rachmat in Kemuning District, Palembang City. This road experiences traffic problems which damage the city's image through the phenomenon of congestion in the area. The aim of this research is to contribute to solving urban problems related to urban transportation in the Basuki Rachmat Palembang area and also to lead to Palembang's local wisdom from a decorative side. This research was conducted using a qualitative descriptive method, data sources from primary and secondary data. The data will be analyzed using a scientific approach, especially in the fields of architecture and urban planning. This research reveals that there are 6 factors that cause traffic jams on Jalan Basuki Rachmat Palembang, namely U-Turn, Jalan Rimba Kemuning, Jalan Rimba Kemuning 1, illegal road control officers, portals that suddenly block u-turns, and drivers' actions against the flow. Then, the image of the Jalan Basuki Rachmat corridor area is in the form of a district and is dominated by a shopping district for goods and services. The solution to combating congestion at U-turns is to plan horseshoe type flyover infrastructure.